Current issues in libraries, information science and related fields - Woodsworth, Anne.; Penniman, William David, 1937- (Bingley, U.K. : Emerald, 2015)
This volume is unusual in that the theme is quite broad in scope yet focused on a specific topic; innovations and boundary-pushing studies in areas not usually found in library literature. It represents a look at the periphery of the field surveyed in previous volumes and presents chapters grouped into two categories: professional issues and transforming services. First section chapters include the challenges facing librarians in an age of litigiousness and threats to academic freedom, educating ethical leaders for the information society by adopting practices from business, valuing intellectual capital assets by looking at the role of librarians in a knowledge society, and emerging practices of open peer review as a means of achieving a "new science". In the second section chapters include the effects of terminology on health queries by analysing users health literacy and topic familiarity, an analysis of academic social networking via a case study of users information behaviour, a study on redefining services and spaces for graduate student success by creating a "scholars' commons", and a final chapter on serving adults and teens in social spaces within a "virtual branch".
Librarians in a litigious age and the attack on academic freedom / Mary Kandiuk, Harriet Sonne de Torrens -- Educating ethical leaders for the information society : adopting babies from business / Maureen L. Mackenzie -- The role of librarians in a knowledge society : valuing our intellectual capital assets / Denise A.D. Bedford, Jennifer K. Donley, Nancy Lensenmayer -- Open peer review : fast forward for a new science / Samir Hachani -- Effects of terminology on health queries : an analysis by user's health literacy and topic familiarity / Carla Teixeria Lopes, Cristina Riberio -- Academic social networking : a case study on users' information behavior / Anamika Megwalu -- The scholars' commons : redefining services and spaces for graduate student success / Michael Perini, Beth Roszkowski -- The social library in the virtual branch : serving adults and teens in social spaces / Abigail Philips, Lorri Mon.
Includes index.
Print version record
Keywords: Language Arts & Disciplines -- Library & Information Science -- General; Library & information services; Library science; Information science